Concepts and advances in information knowledge management : studies from developing and emerging economies - Bwalya, Kelvin Joseph, 1979-; Mnjama, Nathan Mwakoshi; Sebina, Peter Mazebe II Mothataesi, 1970- (Oxford : Chandos Publishing, 2013)
Effective information and knowledge resource management is a driver of competiveness. Many developing countries have put mechanisms in place that seek to match knowledge-based economies, where information has become the fuel for responsiveness, innovation, and competition. Concepts and Advances in Information Knowledge Management brings out emerging and current discussion from the sub-fields of information management in this environment. This title consists of sections on key aspects of information knowledge management and addresses knowledge management, library studies, archives and records management, and information systems.
Part 2 The emerging informat ion management landscape5 Analysing the future of zimbabwe's academic libraries: from their historical past to preparedness for current realities and requirements; Current realities in academic libraries in general; Current realities in academic libraries in Zimbabwe; The education of academic librarians in Zimbabwe; Accreditation and international recognition of library schools in Zimbabwe; The role and impact of Zimbabwean librarian professional bodies; The future of academic libraries and implications for the Zimbabwe context.
CIP data; resource not viewed.
Keywords: Knowledge management -- Developing countries; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Knowledge management; Developing countries; Electronic books; Electronic books